Micro-computed tomography evaluation of bone architecture in various forms of unilateral condylar hyperplasia - Machoň, V; Bartoš, M; Suchý, T; Levorová, J; Foltán, R (International journal of oral and maxillofacial surgery, 2023)
Condylar hyperplasia is one of the causes of facial asymmetry and malocclusion, characterized by enlargement of the lower jaw due to excessive condyle growth activity. The aim of this study was to use micro-computed tomography (micro-CT) to evaluate the bone architecture of the condylar head and determine whether there are differences between patients with various forms of unilateral condylar hyperplasia (UCH): hemimandibular hyperplasia, elongation, and mixed form. The cohort consisted of 28 patients with a mean age of 21.9 years. All patients underwent surgical treatment (condylar shaving) for active pathological growth activity. The portion of the condylar head removed was imaged by micro-CT and subsequently evaluated. Micro-CT imaging and semiquantitative and quantitative evaluation of the bone structure (percentage bone volume, surface density, trabecular thickness, trabecular separation, degree of anisotropy, and porosity of the subchondral bone) did not reveal significant differences between the individual types of condylar hyperplasia (P > 0.05). There were no significant differences in bone structure between the anterior and posterior portions of the condylar head. No statistically significant differences between individual groups of UCH were found in the micro-CT evaluation of the condylar head bone architecture.
Keywords: Mandibular osteotomy; X-ray micro-CT; Hyperplasia; rentgenová mikrotomografie; Mandibular Condyle; Temporomandibular joint disorders; Adult; mladý dospělý; asymetrie obličeje; Facial Asymmetry; processus condylaris mandibulae; Mandible; Mandibular condyle; Young Adult; Humans; hyperplazie; mandibula; dospělí; Temporomandibular joint; lidé; X-Ray Microtomography